Virtual Tourism as a Social Entrepreneurship Model for the Economic Recovery of Tourism Villages (Desa Wisata) in Bali - Zaki, Amin; Ng, Isabelle; Mahdavi, Leila (Yayasan Adra Karima Hubbi, 2025)
The COVID-19 pandemic severely disrupted Bali’s tourism-based economy, forcing rural tourism villages (desa wisata) to explore innovative recovery strategies. The emergence of virtual tourism offers a transformative model that integrates digital technology with social entrepreneurship to sustain community livelihoods and promote cultural preservation. This research aims to analyze virtual tourism as a social entrepreneurship framework that supports economic revitalization, empowerment, and sustainability in Bali’s tourism villages. The study employs a qualitative descriptive design using case studies from selected villages that have implemented virtual tourism platforms between 2021 and 2023. Data were gathered through in-depth interviews with local entrepreneurs, community leaders, and tourism officials, complemented by documentation and online content analysis. The findings reveal that virtual tourism fosters digital inclusion, diversifies income streams, and strengthens social capital through participatory management and local innovation. The model promotes inclusive economic recovery by enabling small-scale entrepreneurs to market cultural experiences globally while maintaining environmental and social ethics. The research concludes that virtual tourism represents an adaptive, community-driven approach to post-pandemic resilience, aligning with the Sustainable Development Goals (SDGs) and Bali’s vision of sustainable cultural tourism.